Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928 - Gąsiorek, Piotr; Degma, Peter (Zootaxa, 2018)
During a faunistic survey in the Pieniny and Tatra Mountains three species of Echiniscidae new to Poland, including one new to science, were found. Bryodelphax instabilis sp. nov. is characterised by an instable number of ventral plates, deep faceting of the scapular plate, having dorsal plates covered either with pseudopores or pores, and striking sexual dimorphism. Two first records, namely Echiniscus militaris and E. spiniger, are rare taxa of upland-mountain character, which have already been reported from a few European countries since the original description at the beginning of the XXth century. The interspecific appendage length variability and development of pedal plates in the spinulosus group, to which E. spiniger belongs, and their taxonomic importance is discussed. Notes relating to sexual dimorphism within the newly recorded Pseudechiniscus facettalis, are also presented. Echiniscus testudo is reported from the Polish part of the Tatra Mountains for the first time. Succeeding findings confirm the high tardigrade α-diversity in the Polish mountain ranges. An amended key for Polish Heterotardigrada is provided.